PENGARUH KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA KEPADA LOYALITAS PELANGGAN (Studi Di Koperasi Artha Prima Cabang Jatisari Semarang) - Dhika Septiawan, 13.05.51.0228; Rizal, Alimuddin (Students' Journal of Economic and Management, 2018)
This study aims to measure the level of customer satisfaction and loyality by examining variable that effect the identification of customer satisfaction and loyality with Koperasi Artha Prima Jatisari Semarang. After a review of lerated literature, in this study determined significant variables that allegedly effect customer satisfaction and loyality, which is variables quality of service that includes dimentions of physical evidance, reliability,security, responsiviness and empathy and variable customer value can be seen as a basis of the development strategy of customer satisfaction leads to loyality. Respondents were selected using purposive sampling technique. With a total sample of 100 customer Koperasi Artha Prima cabang Jatisari Semarang. The data were analyzed using factor analysis to tes validity of the item in question, and the formula Cronbach’sAlpha to test the reability of the instrumen. The data analysis technique used in this study was SPSS 19. Which is used to test the 5 (five) hypotheses that have been developed. The test result showed that the (1) quality of service to customer satisfaction showed a positive and significant, (2) customer value to customer satisfaction showed a positive and significant, (3) customer satisfaction to customer loyality showed a positive and significant,(4) quality of service to customer loyality showed a positive and significant, (5) customer value to customer loyality showed a positive and significant.Keyword : Service Quality, Costumer Value, Costumer Saticfaction and Costumer Loyalty.